1984
DOI: 10.1099/0022-1317-65-10-1803
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Proteins of Chick Embryo Lethal Orphan Virus (Fowl Adenovirus Type 1)

Abstract: SUMMARYChick embryo lethal orphan (CELO) virus (fowl adenovirus type 1) contains at least 14 structural proteins with polypeptide molecular weights ranging from 100K to about 6K. A nomenclature of the CELO virion polypeptides is presented and the molar proportion of each polypeptide has been estimated. The CELO virus pentons were specifically released from the virion by dialysis against borate-based calciummagnesium saline. The penton base (polypeptide III, mol. wt. 92K) and two fibres were separated, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…They are smaller than those of Ad 2 (48k and 18.5k), more closely resenable those of FAV-1 (20k, 12k, and 9.5k) [29,33], and might be the two smallest polypeptides reported for group II avian adenoviruses [30]. The t2k and 9.5k proteins of FAV-1 might be the counterparts of the 12.5k and 9.5k proteins of HEV, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…They are smaller than those of Ad 2 (48k and 18.5k), more closely resenable those of FAV-1 (20k, 12k, and 9.5k) [29,33], and might be the two smallest polypeptides reported for group II avian adenoviruses [30]. The t2k and 9.5k proteins of FAV-1 might be the counterparts of the 12.5k and 9.5k proteins of HEV, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Methods for growth, radioactive labelling, purification and titration of viruses, and for polyacrylamide gel electrophoresis (PAGE) have been described (Laver et al, 1971 ;Younghusband & Bellett, 1971: Braithwaite et aL, 1983Li et aL, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…[35S]Methionine-labelled bands were cut from polyacrylamide gels, digested with chymotrypsin, and the resulting peptides mapped as described (Li et al, , 1984.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After scanned and analyzed by automatic gel image-forming and analyzing system, the molecular mass and relative percentage of each structural polypept ide were obtained ( Table 1). The fact that VP 4 , VP 7 , VP 8 , VP 9 and VP 14 were the main structural polypeptides and made up about 90.2622% of the gross protein revealed that NGVEV fulfilled the criteria of adenovirus to great extent [17,[26][27][28] . From the relationship between DNA base number and the molecular mass of the encoded protein, it is known that NGVEV structural protein with an overall molecular weight of 71 300 D needed DNA of approximately 19.3 kb to code for.…”
Section: Virus Purification and Viral Structural Polypeptide Analysismentioning
confidence: 99%